BRITISH PARLIAMENTARY DEBATING SYSTEM IN IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT - Yunda Lestari; Awalludin Awalludin (STKIP PGRI Lubuklinggau, 2018)
The aim of this study is to find out whether or not is there any significantly improvement on students’ speaking achievement who are taught by using British Parliamentary Debating System. The study was conducted as an experimental method. Non-equivalent control group design will be applied in this study. The population was all semester students of English Education Study Program of Baturaja University in the academic year 2017/2018 with the total number of population were 118. Cluster random sampling was used in taking the sample. The total numbers of students as sample were 51 students. There were three raters who will be involved in working and scoring the oral tests of speaking achievement. Based on the result of data analysis, the significant (2-tailed) between pre- and post- test in experimental group was 0,000 which means there was significant improvement in experimental group, while the significant (2-tailed) between pre- and post- test in control group was 0,677 which means there was no significant improvement in control group. The mean difference in the independent sample t-test between experiment and control group was 21.537. It indicated that there was a significant difference in students’ speaking achievement between those who were taught by using British Parliamentary Debating System and those who were not.